Eksplorasi Pendekatan Team Teaching dalam Mengelola Fokus Belajar Siswa Kelas II: Studi Kasus di MI Unggulan Al Muhammad Cepu - Burhanudin Afandi; Karjo Karjo; Afni Firdausia; Siti Nur Hidayah; Jarir Idris (AL-THIFL : Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The management of the learning focus of low-grade students at Madrasah Ibtidaiyah (MI) is often a complex challenge due to the limitations of attention spans and crowded classroom dynamics. This qualitative research with a single case study design was conducted to explore in depth the implementation of the team teaching approach in managing the learning focus of Class II students at MI Unggulan Al Muhammad Cepu. Data were collected through participant observation over 16 meetings, in-depth interviews with two team teachers and six students, and analysis of lesson planning documents. The objectives of the study are to (1) identify the mechanism of applying the team teaching model, (2) analyze its impact on the pattern and duration of learning focus (time-on-task), and (3) explore the perception of teachers and students. The results of the study revealed that team teaching develops into a dynamic pedagogical symphony supported by three core mechanisms: collaborative planning with role scenarios, non-verbal microcognitive communication, and hierarchical responsiveness. This implementation succeeded in increasing time-on-task from thirty-five percent to eighty percent 80% and transformed the focus pattern from fragmented to sustained attention, while creating a learning ecosystem that is cognitively efficient and psychologically safe for students. These findings offer a practical model of collaborative learning management in the early classroom that is holistic and contextual.